High-refractive-index composition for optical material as well as preparation method and application of high-refractive-index composition

By using the oligomer and inorganic nanoparticle compositions generated by copolymerization of specific monomers in the photocuring resin, the problems of low refractive index and uneven dispersion of inorganic nanoparticles of the photocuring resin are solved, and optical materials with high refractive index and good performance are achieved.

CN119708489AInactive Publication Date: 2025-03-28WUHAN SUNSHINE OPTOELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937011.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The refractive index of existing photocuring resins is low, making it difficult to evenly disperse inorganic nanoparticles, resulting in limited refractive index increase.

Method used

A high refractive index composition consisting of oligomers, inorganic nanoparticles, initiators and additives copolymerized with specific monomers is used to increase the refractive index and enhance compatibility through click chemical reactions and photo-induced polymerization.

Benefits of technology

It achieves a high refractive index optical material, with good storage stability, mechanical properties and optical properties, and can effectively improve the system efficiency of optical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211741820000021
    Figure BDA0005211741820000021
  • Figure BDA0005211741820000022
    Figure BDA0005211741820000022
  • Figure BDA0005211741820000043
    Figure BDA0005211741820000043
Patent Text Reader

Abstract

The invention belongs to the technical field of optical materials, and particularly relates to a high-refractive-index composition for an optical material as well as a preparation method and application of the high-refractive-index composition. The preparation method comprises the following steps: reacting a dimercapto compound with the same or different dimercapto compounds, or reacting the dimercapto compound with a compound containing an unsaturated group at the tail end, and adopting a click chemical reaction between mercapto groups or between mercapto groups and double bonds to obtain a high-refraction oligomer; after the reaction is finished, a high-refractive-index composition element for the optical material is reserved on a main chain, and the content of the high-refractive-index composition element for the optical material in the finally obtained oligomer is very high, so that the refractive index is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical materials, and specifically relates to a high refractive index composition for optical materials and a preparation method and application thereof. Background Art

[0002] In many current application fields, such as optical communication technology, photonic computers, and display panels, high refractive index materials are needed for photon integration to increase system efficiency or protect devices. However, the refractive index of most photocurable resins is relatively low, generally in the range of 1.45 to 1.55. It is usually necessary to add a certain amount of inorganic nanoparticles to the photocurable resin to increase the refractive index of the photocurable resin. Moreover, the more inorganic nanoparticles are added, the more obvious the improvement in the refractive index of the photocurable resin. However, inorganic nanoparticles are inorganic materials, and photocurable resins are organic materials. The two are incompatible, and it is difficult for inorganic nanoparticles to be evenly dispersed in photocurable resins. Therefore, being able to provide a compound with a high refractive index has become one of the problems to be solved in this field. Summary of the invention

[0003] In order to solve the deficiencies of the prior art, the present invention provides a high refractive index composition for optical materials and a preparation method and application thereof.

[0004] The technical solution provided by the present invention is as follows:

[0005] A high refractive index composition for optical material, comprising:

[0006] (1) An oligomer formed by copolymerization of one or more monomers represented by Formula 1, wherein the general formula of Formula 1 is as follows:

[0007]

[0008] (2) Inorganic nanoparticles;

[0009] (3) initiator;

[0010] (4) additives;

[0011] In formula 1:

[0012] R a Selected from the following substituted or unsubstituted groups: C1-C36 alkyl, C1-C6 alkoxy (the number of oxygen is one, two or three), C3-C30 heterocycloalkyl, C6-C48 monocyclic aromatic hydrocarbons, polycyclic aromatic hydrocarbons or condensed aromatic hydrocarbons, C3-C48 heteroaromatic hydrocarbons;

[0013] R b Selected from mercapto, ethylenically unsaturated hydrocarbon groups containing a carbonyl group, each R b are the same or different, and each R of at least one monomer represented by Formula 1b The ethylenically unsaturated hydrocarbon group is selected from a mercapto group, and the carbonyl-containing ethylenically unsaturated hydrocarbon group is preferably an ethylenically unsaturated hydrocarbon group having a carbonyloxy group or an ethylenically unsaturated hydrocarbon group having a carbonylthio group;

[0014] The oligomer at least comprises a C3-C30 heterocycloalkyl structural unit, wherein the number of heteroatoms is at least one, and each heteroatom is independently selected from N, O or S atoms.

[0015] Specifically, the formula 1 is specifically selected from the general formulas shown in formulas 1-1, 1-2, and 1-3:

[0016]

[0017] Furthermore, the monomer contains at least the compound described in Formula 1-1;

[0018] R1 is selected from the following substituted or unsubstituted groups: C1-C36 alkyl, C3-C30 heterocycloalkyl, C6-C48 monocyclic aromatic hydrocarbon, C10-C48 polycyclic aromatic hydrocarbon; X is O, S; R2 is selected from H or methyl.

[0019] Further:

[0020] The oligomer is formed by copolymerization of one or more monomers described in formula 1-1;

[0021] Alternatively, the oligomer is copolymerized by at least one monomer described in Formula 1-1 and at least one monomer described in Formula 1-2;

[0022] Alternatively, the oligomer is copolymerized by at least one monomer described in Formula 1-1 and at least one monomer described in Formula 1-3;

[0023] At least one of the monomers R a Selected from C3-C30 heterocycloalkyl.

[0024] The degree of polymerization is 1-3000, preferably 2-1000, more preferably 2-50. In the embodiment of the present application, the degree of polymerization is preferably 10-20.

[0025] That is, in the technical solution of the present application, among the monomers used to synthesize the oligomer, at least one monomer has an R a The group consisting of C3-C30 heterocycloalkyl groups includes at least one N, O or S atom substitution.

[0026] Further preferably, the oligomer in the technical solution of the present application is obtained by copolymerizing a monomer having the structural formula 1-1 with a monomer having the structural formula 1-2 or a monomer having the structural formula 1-3. Moreover, in the monomer having the structural formula 1-1, R1 is selected from a C3-C30 heterocycloalkyl group substituted with at least one N, O or S atom.

[0027] Further preferably, the oligomer in the technical solution of the present application is obtained by copolymerizing a monomer having the structural formula 1-1 with a monomer having the structural formula 1-3.

[0028] Preferably, R1 is selected from the following substituted or unsubstituted groups: C1-C20 alkyl, C3-C15 heterocycloalkyl, C6-C18 monocyclic aromatic hydrocarbons, C10-C18 polycyclic aromatic hydrocarbons.

[0029] In a preferred technical solution, the C1-C20 alkyl group is selected from unsubstituted C1-C10 straight-chain alkyl groups.

[0030] In the preferred technical solution, the C3-C30 heterocycloalkyl group is selected from at least one C3-C15 saturated or unsaturated heterocycloalkyl group selected from N, O and S; the C3-C15 heterocycloalkyl group includes at least one S atom substitution, examples of which include but are not limited to a five-membered ring, a six-membered ring or a seven-membered ring, and the number of S atoms is one, two or three.

[0031] In a preferred technical solution, the C3-C15 heterocycloalkyl group including at least one S atom substitution also has at least one N atom substitution.

[0032] In the preferred technical solution, the C6-C18 monocyclic aromatic hydrocarbon is preferably an unsubstituted phenyl.

[0033] Furthermore, the multiple phenyl groups in the C10-C48 polycyclic aromatic hydrocarbons are connected by any one or more of -S-, -O-, single bond, -C(=O)-, -S(=O)-2, -NR3-, and the R3 is selected from a C1-10 straight chain or branched alkyl group.

[0034] Further, when X in Formula 1-3 is selected from O, R1 contains at least one S atom. And R1 is preferably a C10-C48 polycyclic aromatic hydrocarbon. Further preferably, the C10-C48 polycyclic aromatic hydrocarbon is selected from two phenyl groups, and the phenyl groups are connected by any one or two of -S-, -O-, a single bond, -C(=O)-, -S(=O)2-, -NR3-, and R3 is selected from a C1-10 straight chain or branched alkyl group.

[0035] Further preferably, the aryl group having 6 to 24 carbon atoms has the following structural formula:

[0036] R6 is selected from an alkyl group having 1 to 5 carbon atoms, O, S, C=O, SO2, NR5, wherein R5 is selected from an alkyl group having 1 to 5 carbon atoms, is empty or a single bond; R7 and R8 are independently selected from alkyl groups having 1 to 5 carbon atoms, O, S, C=O, SO2, and NR9, and R9 is selected from alkyl groups having 1 to 5 carbon atoms.

[0037] More preferably, R7 and R8 are the same and are selected from O or S.

[0038] For example, the aryl group having 6 to 24 carbon atoms may be selected from the following:

[0039]

[0040] Furthermore, the initiator is used to initiate the polymerization of the polymerizable compound, and a photoinitiator is selected, specifically any one of α-hydroxy ketone initiators, benzoin initiators, acylphosphine oxide initiators, acetophenone initiators, morpholinyl ketone initiators, naphthylimide photoinitiators, oxime ester photoinitiators, and carbazole-based photoinitiators, or a combination of at least two thereof.

[0041] Preferably, the photoinitiator is selected from at least one of diphenyl (2,4,6-triformyl) phosphine oxide, phenyl (2,4,6-trimethylbenzoyl) phosphonic acid ethyl ester, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-benzyl-2-dimethylamino-1- (4-morpholinophenyl) butanone, 1-hydroxycyclohexyl phenyl ketone, commercially available OXE-01 model photoinitiator, and commercially available OXE-02 model photoinitiator.

[0042] Furthermore, the resin composition also includes the following components in weight percentage: 0%-60% of surface modified or unmodified inorganic nanoparticles with a refractive index ≥1.8, and / or 2%-20% of (meth)acrylate monomers containing aromatic hydrocarbon groups or aliphatic hydrocarbon groups.

[0043] Preferably, the surface-modified or unmodified inorganic nanoparticles are selected from oxides or sulfides of at least one metal element selected from zirconium (Zr), titanium (Ti), zinc (Zn), germanium (Ge), niobium (Nb), molybdenum (Mo), indium (In), tin (Sn), antimony (Sb), cerium (Ce), neodymium (Nd), hafnium (Hf), tantalum (Ta), and bismuth (Bi). More preferably, they are oxides or sulfides of 1 to 2 metal elements.

[0044] The inorganic nanoparticles are selected from any one of ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, and Nd2O3, or a combination of at least two thereof, wherein the average particle size of the inorganic nanoparticles is 10-50 nm.

[0045] The surface modification methods include esterification, coupling agent method, surface grafting method, organic adsorption coating method, etc. For example, the inorganic nanoparticles can be surface modified by a silane coupling agent to improve compatibility and dispersibility with the main resin material. In this embodiment, KH-560 silane coupling agent is used to perform surface modification on the nanoparticles by a coupling agent method.

[0046] Preferably, the (meth)acrylate monomer is a (meth)acrylate monomer containing a C1-12 alkane group substituted or unsubstituted by a hydroxyl group, or a (meth)acrylate monomer containing a C1-12 alkyl ether group substituted or unsubstituted by a hydroxyl group, or a (meth)acrylate monomer containing 1-2 benzene ring structures substituted or unsubstituted by an alkyl group or a hydroxyl group. The (meth)acrylate monomer specifically includes: mono(meth)acrylate, di(meth)acrylate, tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate or hexa(meth)acrylate.

[0047] Preferred examples of the (meth)acrylate monomer having an aliphatic hydrocarbon group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, cyclohexyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, octanediol di(meth)acrylate, di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or a mixture of at least two thereof, but is not limited thereto.

[0048] The (meth)acrylate monomer having an aromatic hydrocarbon group may preferably be exemplified by bisphenol A di(meth)acrylate, bisphenol A polyoxyethylene ether di(meth)acrylate, benzyl (meth)acrylate, 4-biphenylmethanol (meth)acrylate, [1,1'-biphenyl]-4,4'-diyl di(meth)acrylate, or a mixture of at least two thereof, but is not limited thereto.

[0049] Furthermore, a solvent may be added to the technical solution of the present application, and an organic solvent is further preferred, and the organic solvent may be selected from, but is not limited to, one or a mixture of at least two of esters, alcohols, ethers, ketones, and benzenes. Specific examples include: ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-butyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, methoxybutyl acetate, methanol, ethanol, cyclohexanol, ethylene glycol, propylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-butyl ether, acetone, methyl amyl ketone, methyl isopropyl ketone, methyl isoamyl ketone, diisopropyl ketone, diisobutyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, and xylene.

[0050] Among the above solvents, propylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and toluene are preferred because of their excellent solubility and dispersibility in the resin composition components.

[0051] Furthermore, auxiliary agents such as surfactants, adhesion promoters, thermal stabilizers, defoaming agents, etc. may be selectively added to the high refractive index composition for optical materials according to needs.

[0052] Among them, the surfactant, adhesion promoter, heat stabilizer and defoaming agent can all be commercially available products.

[0053] In a second aspect, a method for preparing a high refractive index composition for an optical material comprises the following steps:

[0054] 1) Preparation of oligomers from monomers, wherein:

[0055] At least one of the monomers has two terminal thiol groups;

[0056] Alternatively, at least one of the monomers has two terminal thiol groups, and at least one of the monomers has two terminal unsaturated hydrocarbon groups and a sulfur atom;

[0057] 2) The oligomer, inorganic nanoparticles, initiator and auxiliary agent obtained in step 1) are uniformly mixed to obtain a high refractive index composition for optical materials.

[0058] In a third aspect, a high refractive index composition for optical material is used, wherein the high refractive index composition for optical material is used in display devices, optical lenses and optical devices.

[0059] According to the technical scheme of the present invention, a dithiol compound is reacted with the same or different dithiol compounds, or a dithiol compound is reacted with a compound containing an unsaturated group at the end, and a click chemistry reaction between thiol groups or between thiol groups and double bonds is used to obtain a high-refractive oligomer. After the reaction is completed, a high-refractive index composition element for optical materials will be retained on the main chain. The content of a high-refractive index composition element for optical materials in the finally obtained oligomer is very high, so that the refractive index is greatly improved. Furthermore, the monomer containing an unsaturated group contains a large number of benzene rings, so the resin obtained after the reaction contains a large number of rigid benzene ring structures, so the obtained optical resin has good heat resistance.

[0060] The oligomer of the technical solution of the present invention has good compatibility with the inorganic nanoparticles, so that the inorganic nanoparticles are evenly dispersed in the composition and have good storage stability, so that the composition has a high refractive index and good mechanical and optical properties. DETAILED DESCRIPTION

[0061] The principles and features of the present invention are described below. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0062] In the embodiment, the inorganic nanoparticles are added in the form of being mixed with a commercially available dispersant: the dispersing solvent is commercially available PGMEA (propylene glycol methyl ether acetate), and the wt% of the inorganic nanoparticles is 40-60%. In this embodiment, the mass fraction of the inorganic nanoparticles is 50%.

[0063] Synthesis Example:

[0064] Example 1: A1

[0065]

[0066] In a 50 ml flask, (2.82 g, 10 mmol) S1-1 (CAS: 37116-97-5) and (0.09 g, 1 mmol) S1-2 (CAS: 540-63-6) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A1 with a molecular weight Mw = 5582.

[0067] Example 2: A2

[0068]

[0069] In a 50 ml flask, (2.12 g, 10 mmol) S2-1 (CAS: 136122-15-1) and (0.09 g, 1 mmol) S2-2 (CAS: 540-63-6) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A2 with a molecular weight of Mw = 4834.

[0070] Example 3: A3

[0071]

[0072] In a 50 ml flask, (1.48 g, 10 mmol) S3-1 (CAS: 22511-31-5) and (0.09 g, 1 mmol) S3-2 (CAS: 540-63-6) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A3 with a molecular weight Mw = 4286.

[0073] Example 4: A4

[0074]

[0075] In a 50 ml flask, (0.94 g, 10 mmol) S4-1 (CAS: 540-63-6) and (0.37 g, 1 mmol) S4-2 (CAS: 1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A4 with a molecular weight Mw = 6962.

[0076] Example 5: A5

[0077]

[0078] In a 50 ml flask, (1.52 g, 10 mmol) S5-1 (CAS: 856940-26-6) and (0.39 g, 1 mmol) S5-2 (CAS: 129283-82-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A5 with a molecular weight Mw = 7534.

[0079] Example 6: A6

[0080]

[0081] In a 50 ml flask, (1.84 g, 10 mmol) S6-1 (CAS: 645404-26-8) and (0.37 g, 1 mmol) S6-2 (CAS: 1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A6 with a molecular weight Mw = 8312.

[0082] Example 7: A7

[0083]

[0084] In a 50 ml flask, (1.48 g, 10 mmol) S7-1 (CAS: 22511-31-5) and (0.36 g, 1 mmol) S7-2 (CAS: 103489-89-0) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A7 with a molecular weight Mw = 7030.

[0085] Example 8: A8

[0086]

[0087] In a 50 ml flask, (1.5 g, 10 mmol) S8-1 (CAS: 132120-63-9) and (0.37 g, 1 mmol) S8-2 (CAS: 1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A8 with a molecular weight Mw = 7802.

[0088] Example 9: A9

[0089]

[0090] In a 50 ml flask, (1.5 g, 10 mmol) S9-1 (CAS: 132120-63-9) and (0.34 g, 1 mmol) S9-2 (CAS: 2425533-68-0) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A9 with a molecular weight of Mw = 7842.

[0091] Example 10: A10

[0092]

[0093] In a 50 ml flask, (1.5 g, 10 mmol) S10-1 (CAS: 132120-63-9) and (0.26 g, 1 mmol) S10-2 (CAS: 6606-59-3) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain A10 with a molecular weight Mw = 6062.

[0094] Example 11: A11

[0095]

[0096] In a 50 ml flask, (1.5 g, 10 mmol) S11-1 (CAS: 132120-63-9) and (0.18 g, 1 mmol) S11-2 (CAS: 14970-87-7) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C1 with a molecular weight Mw = 5250.

[0097] The synthesis examples of the present invention prepare compounds A1-A11 with a polymerization degree n in the range of 15-20.

[0098]

[0099]

[0100] B1: n-pentyl acrylate;

[0101] B2: bisphenol A dimethacrylate;

[0102] B3: pentaerythritol tetraacrylate;

[0103] C1: ZrO2;

[0104] C2: TiO2;

[0105] D1: diphenyl (2,4,6-triformyl) phosphine oxide;

[0106] D2: acryloxy-modified silane polymer (commercially available surfactant);

[0107] D3: Propylene glycol methyl ether.

[0108] Performance testing:

[0109] The quartz substrate was coated with 5 μm of inkjet printing technology, dried in a vacuum oven for 30 minutes, and then pre-baked on a vacuum hot plate at 80 ° C for 1 minute. 2 The organic-inorganic composite material is irradiated with an intensity of to solidify it to prepare a thin film sample.

[0110] 1) The refractive index and extinction coefficient of A1-A11 were measured using an Abbe refractometer, as shown in Table 1;

[0111] 2) Light transmittance: The transmittance of the prepared film was measured using a spectrophotometer; the test results are shown in Table 2 below;

[0112] 3) Hardness: The hardness was tested using a Shore D hardness tester. The test results are shown in Table 2 below.

[0113] 4) Yellowness Index YI: measured using a Hitachi spectrophotometer. The test results are shown in Table 2 below:

[0114] Table 1

[0115]

[0116] Table 2

[0117]

[0118] As can be seen from the above table, the high refractive index composition for optical materials prepared by the present invention has good storage stability and good tensile strength. Compared with conventional UV glue, the sulfur-containing oligomer has good compatibility with inorganic nanoparticles, and the obtained high refractive index composition for optical materials has high refractive index, and the optical properties and mechanical properties are significantly improved.

[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high refractive index composition for optical material, characterized in that: include: (1) An oligomer formed by copolymerization of one or more monomers represented by Formula 1, wherein the general formula of Formula 1 is as follows: (2) Inorganic nanoparticles; (3) initiator; (4) additives; In formula 1: R a Selected from the following substituted or unsubstituted groups: C1-C36 alkyl, C1-C6 alkoxy, C3-C30 heterocycloalkyl, C6-C48 monocyclic aromatic hydrocarbons, polycyclic aromatic hydrocarbons or condensed aromatic hydrocarbons, C3-C48 heteroaromatic hydrocarbons; R b Selected from mercapto, ethylenically unsaturated hydrocarbon groups containing a carbonyl group, each R b are the same or different, and each R of at least one monomer represented by Formula 1 b Selected from thiol; The oligomer at least comprises a C3-C30 heterocycloalkyl structural unit, and the C3-C30 heterocycloalkyl has at least one N, O or S atom substituted.

2. The high refractive index composition for optical material according to claim 1, characterized in that: The formula 1 is specifically selected from the general formulas shown in formulas 1-1, 1-2, and 1-3: Furthermore, the monomer contains at least the compound described in Formula 1-1; R1 is selected from the following substituted or unsubstituted groups: C1-C36 alkyl, C3-C30 heterocycloalkyl, C6-C48 monocyclic aromatic hydrocarbon, C10-C48 polycyclic aromatic hydrocarbon; X is O, S; R2 is selected from H or methyl.

3. The high refractive index composition for optical material according to claim 2, characterized in that: The oligomer is formed by copolymerization of one or more monomers described in formula 1-1; Alternatively, the oligomer is copolymerized by at least one monomer described in Formula 1-1 and at least one monomer described in Formula 1-2; Alternatively, the oligomer is copolymerized by at least one monomer described in Formula 1-1 and at least one monomer described in Formula 1-3; At least one of the monomers R a Selected from C3-C30 heterocycloalkyl.

4. The high refractive index composition for optical material according to claim 3, characterized in that: The C3-C30 heterocycloalkyl group is selected from a C3-C15 saturated or unsaturated heterocycloalkyl group, wherein the number of its heteroatom is at least one, and each heteroatom thereof is independently selected from a N, O or S atom.

5. The high refractive index composition for optical material according to claim 3, characterized in that: In the C10-C48 polycyclic aromatic hydrocarbons, multiple phenyl groups are connected by any one or more of -S-, -O-, single bond, -C(=O)-, -S(=O)2-, and -NR3-, and R3 is selected from a C1-10 straight chain or branched alkyl group.

6. The high refractive index composition for optical material according to claim 2, characterized in that: At least one monomer of formula 1-3 satisfies the following conditions: X is selected from O, and R1 contains at least one S atom.

7. The high refractive index composition for optical material according to claim 1, characterized in that: The high refractive index composition for optical materials further includes a (meth)acrylate monomer containing an aromatic hydrocarbon group or an aliphatic hydrocarbon group.

8. The high refractive index composition for optical material according to claim 1, characterized in that: The inorganic nanoparticles are selected from surface-modified or unmodified inorganic nanoparticles, and the inorganic nanoparticles are selected from any one or a combination of at least two of ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, and Nd2O3.

9. A method for preparing a high refractive index composition for optical materials according to any one of claims 1 to 8, characterized in that: The steps include: 1) Preparation of oligomers from monomers, wherein: At least one of the monomers has two terminal thiol groups; Alternatively, at least one of the monomers has two terminal thiol groups, and at least one of the monomers has two terminal unsaturated hydrocarbon groups and a sulfur atom; 2) The oligomer, inorganic nanoparticles, initiator and auxiliary agent obtained in step 1) are uniformly mixed to obtain a high refractive index composition for optical materials.

10. Use of the high refractive index composition for optical materials according to any one of claims 1 to 8, characterized in that: For preparing display devices or optical devices; Alternatively, it can be used to prepare optical lenses.